Water barrier properties of starch films reinforced with cellulose nanocrystals obtained from sugarcane bagasse - Slavutsky, Anibal Marcelo (2014)
Water transport in edible films based on hydrophilic materials such as starch, is a complex phenomenon due to the strong interaction of sorbed water molecules with the polymeric structure. Cellulose nanocrystals (CNC) were obtained from sugarcane bagasse. Starch and starch/CNC films were formulated and their water barrier properties were studied. The measured film solubility, contact angle, and water sorption isotherm indicated that reinforced starch/CNC films have a lower affinity to water molecules than starch films. The effects that the driving force and the water activity (aw) values at each side of the film have on permeability were analyzed. Permeability, diffusivity, and solubility coefficients indicated that the permeation process depends mostly on the tortuous pathway formed by the incorporation of CNC and therefore were mainly controlled by water diffusion. The interaction between CNC and starch chain is favoured by the chemical similarities of both molecules.